Assessment of Program Delivery to Small Farmers: Fax Information Center System at Satellite Locations - John G. Richardson; Joey Knight; Fred May; Maurice McAlister (Journal of Applied Communications, 1998)
Due to the many variables associated with small and part-time farmers, such as widely ranging educational levels and available time applied to farming, effectively providing extension information to this group of farmers can be quite difficult. The use of innovative, program delivery methods for reaching small and part-time farmers has been tried in several North Carolina counties with variable success. One means of reaching these special audiences is a satellite information center at agribusiness or other locations away from the extension office itself. A fax request system prominently placed directly in these satellite locations has produced widely variable results in level of use from the perspective of requests for information originating from the centers. Yet, where the centers have been used for both an information request system and an informational bulletin board with timely information sent to the centers from Cooperative Extension for posting on the bulletin boards, the results have been very favorable. While many factors have been found to affect the success of individual locations, the fax satellite centers appear to be able to provide a niche for innovative program delivery by extension and can have highly beneficial side effects of positively marketing the extension programs in the respective counties.